ATTITUDES TOWARDS THE NAMES AND THE TASTES OF FOODS IN SONGKHLA PROVINCE, THAILAND - Angsuviriya, Angsuviriya; Chanokporn, Chanokporn (E-Journal of Cultural Studies; Volume 12, Number 1, February 2019, 2019)
The objective of this article is to study the attitudes of different age and ethnic groups reflected through the names and the taste of food, that is the southern Thais have a positive attitude towards more tasteful or the taste of hot than the other ethnic groups while the Chinese Thais they have a more positive attitude towards  insipid taste than the other ethnic groups. For the Malaysian Thais they have a more positive attitude towards the taste of sweet than the other two ethnic groups. As for main course dish, the most popular main course dishes in all the 3 groups are “Kangsom” (sour soup made of tamarind paste) and “KangTaipla” or “KangPhungpla”. As for dessert, the most favorite desserts in all the 3 groups are “Klauybuatchee” or Klauybuat (banana in coconut milk) and “Lotchong” or “Singaporean Lotchong”. In addition, it is found that the Chinese Thais and the southern Thais have a negative attitude towards beef, eels, buffalo meat etc, while the Malaysian Thais have a negative attitude towards pork because they are Muslim. When age groups have been taken into account, age group 1 (15-25) does not like spicy foods, compared with the other age group. While age group 2 (35-45) has similarities in the food names of those in age group 1 and age group 3; therefore, there are more food names in age group 2 than those in the other groups. In addition, for age group 3 (55 or more) more local names of foods are found.   Keywords : Attitudes, the names and the tastes of foods, the ethnic